Batik Jumputan, Student Creativi Penerapan Batik Jumputan untuk Melatih Kreativitas Siswa Serta Menanamkan Nilai-Nilai Kearifan Lokal di SDN Tlogomas 2 Kota Malang - Grace Maria Giri; Bagus Sugiharto, Firsta; Maria Aprilia; Stevanus Rifaldo Leto; Abdul Hamid; Tomas Surandoko (LPPM UNINUS, 2025)
This study aims to foster students’ creativity and instill local wisdom values through the implementation of batik jumputan activities at SDN Tlogomas 2, Malang City. The background of this research stems from the importance of culturally-based education in shaping character and appreciating local heritage from an early age. The batik jumputan learning activity is considered effective in combining artistic skills with local values such as perseverance, cooperation, and cultural appreciation. This study employed a qualitative approach with a case study design, using observation, in-depth interviews, and documentation as data collection techniques during the period of May 5–9, 2025. Participants included classroom teachers, art and culture teachers, and students involved in the batik-making activities. The results show that batik jumputan activities provide a space for students to express themselves creatively through exploration of colors and patterns, while also enhancing their understanding of local culture. The learning process also fostered a collaborative and enjoyable atmosphere, strengthening social relationships among students. The findings imply that integrating local wisdom into art education plays a strategic role in character formation and cultural identity development. In conclusion, the implementation of batik jumputan at SDN Tlogomas 2 can serve as an effective strategy to cultivate creativity and embed local wisdom values in a contextual and sustainable manner.